Effect of Replacing Noug Seed Cake with Naachi Buuxo (Pentas schimperiana) Leaf on Testicular Parameters, Semen Characteristics, Body Condition Score, and Body Weight Gain of Flushing Bonga Ram - Woldemeskel, Berhanu (Bonga University, 2024)
In Ethiopia, livestock production is affected by feed insufficiency, mostly protein supplements due to unavailability and high costs. Observation of alternative feed sources is unquestionable. Due to this, supplementation with multipurpose fodder shrubs might be an alternative protein source. This study was conducted to evaluate the effect of replacing noug seed cake (NSC) with air-dried Pentas schimperiana leaf (PsL) on testicular parameters, semen characteristics, body condition score (BCS), and BWG of flushing Bonga ram fed on natural pasture as a basal diet. The study involved 48 rams (8-12 months old) and used a randomized complete block design with 6 treatment and 8 replications based on age and BCS. Treatments included 100% concentrate (180g NSC) (T1), 75% NSC (135g) Cp replaced by 25% (45g) air-dried PsL (T2), 50% NSC (90g) Cp replaced by 50% (90g) air-dried PsL (T3), 25% NSC (45g) Cp replaced by 75% (135g) air-dried PsL (T4), 100% NSC (180g) Cp replaced by 100% (180g) air-dried PsL (T5) and control group (T6). The sheep were fed equal amounts of supplements twice a day, containing 450 g/day. In fresh semen, colour, mass motility, concentration, and volume of sperm were measured and also measurements of scrotal circumference (SC), BCS, and BW were taken. Data was analyzed using general linear model procedure (SAS 9.4, 2019). Air-dried PsL, NP, NSC, and WB had CP contents of 21, 7.1, 27.8, and 15.9, respectively. The achieved ADG (g/day) of sheep in T1 (98) and T2 (101.56) were higher (P<0.05) than in T5 (71.34) and T6 (34.24). The BCS was highest (P< 0.05) in T1 (3.87), T2 (3.93), T3 (3.75) and T4 (3.68), but lowest in T5 (3.43) and T6 (3.25). The SC (cm) was significantly higher (P<0.05) for T1 (28.31) and T2 (28.42), but lowest in T5 (26.65) and T6 (25.6). Semen volume (ml) was significantly higher (P<0.05) for T1 (1.41) and T2 (1.45), but lowest for T5 (0.93) and T6 (0.67). Spermatozoa concentration (x109) was significantly higher (P<0.05) for T1 (4.91) and T2 (4.94), but lowest in T5 (3.66) and T6 (3.57). Semen colour and mass MOT were not statistically different (P>0.05) between supplemented and control group. The BCS of rams showed a positive correlation with both semen volume (r=0.47) and SC (r=0.29). Semen volume and the SC had a positive correlation (r=0.50). The present experiment resulted air-dried PsL can replace up to 75% NSC in long term flushing of Bonga rams to improve SC, semen characteristics, BC, and BW than rams supplemented with 100% air-dried PsL alone and ram grazing on NP. This study highlights the beneficial potential of air-dried PsL as a supplement for ruminants fed a basal diet of fibrous feeds. So, further study covers all seasons should be done for investigation of the impact of this shrub leaf on the BW, SC, BCS, and semen characteristics of Bonga rams.